User Experience Analysis on Jamsostek Application Using the UEQ Method - Noer Azni Septiani; Olivia, Cindy (International Journal of Informatics and Computation, 2026)
BPJS Ketenagakerjaan developed the Jamsostek Mobile (JMO) application to provide employment social security services in Indonesia. The application has been downloaded by more than 10 million users and maintains a relatively high rating on the Google Play Store. However, users still report several problems related to system performance, feature functionality, and service quality. Common issues include difficulties in updating personal data, checking account balances, and logging into user accounts. These problems indicate the need to evaluate the user experience of the application. Therefore, this study analyzes the user experience of the JMO application and identifies aspects that require improvement. This study applies the User Experience Questionnaire (UEQ) method because it evaluates six key dimensions of user experience: attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. We collected data from 100 active JMO users and analyzed their responses using the UEQ framework. The results show positive evaluations across all dimensions, with mean scores of 2.140 for attractiveness, 2.283 for perspicuity, 2.280 for efficiency, 1.910 for dependability, 2.145 for stimulation, and 1.790 for novelty. The benchmark analysis places all dimensions in the Excellent category, indicating a highly positive user experience. The findings show that users perceive the JMO application as attractive, easy to understand, efficient, reliable, motivating, and innovative. This paper provides practical insights for developers and supports future improvements to enhance user satisfaction and service quality.